Eating right in the Renaissance - Albala, Ken, 1964- (California studies in food and culture ;, 2002)
Eating right has been an obsession for longer than we think. Renaissance Europe had its own flourishing tradition of dietary advice. Then, as now, an industry of experts churned out diet books for an eager and concerned public. Providing a cornucopia of i.